(3EYOGO GSJQGJjLjI GdJShjb hYedjGJgGs - (3CMeO(B, (3Hf ehjRIs ((3YeGf(B:s (3GdjGRhQj ddfTQ hGdJhRjY(B,s, 2013)
(3jVe eONd aj GdGSJQGJjLjI GdJShjbjI, eQGMd GYOGO GdGSJQGJjLjI GdJShjbjI, GSJQGJjLjGJ GdeRjL GdJShjbj, YedjGJ GdGSJQGJjLjI GdJShjbjIs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs